Arts, creative & cultural initiatives for citizen engagement on climate action: Insights from Ireland's Creative Climate Action Fund - J. Mac Mahon; A. Revez; M. Burke; P. Hogan; M.M. Nyhan (Current Research in Environmental Sustainability)
A national study in Ireland on the impacts of creative and cultural climate action initiatives highlights their potential to act as catalysts for fostering citizen engagement. This research evaluated five distinct creative projects, each addressing critical themes such as sustainable agriculture, circular economy, repair culture, consumption habits, sea-level rise, biodiversity, and community-driven climate action. These initiatives formed part of a government programme to enhance public participation in climate action. Utilising surveys, interviews, observations, and focus groups, data was collected and analysed to understand impacts on participants' cognitive, emotional, and practical engagement with climate issues. The COM-B Behaviour System Model was also employed to assess impacts on participants' capacity, opportunity, and motivation to take climate action. Results showed that interactive, participatory-style creative mediums led by artists and practitioners, such as demonstrations, workshops, presentations, and discussion, effectively engaged participants across cognitive, emotional, and practical dimensions. Respondents reported an increased sense of self-efficacy and capacity to take achievable climate actions. Community-centred, peer-sharing formats emerged as trusted and valued opportunities for accessing relevant climate information, aiding constructive dialogue on complex topics. Artists' unique perspectives and creative expressions generated positive energy and an openness to engage, renewing participants' motivation to act. Nature-based events notably deepened emotional connections to the natural world, a strong motivator of pro-environmental behaviours. The study underscored participants' need for supportive and safe spaces to facilitate sustained climate dialogue and action within their communities. Findings suggest that targeted creative community events can significantly support climate policy efforts by fostering high-quality citizen engagement.